Scrutinizing Norwegian kindergarten teachers’ considerations about talk moves - Justnes, Camilla Normann; Mosvold, Reidar (NOMAD Nordic Studies in Mathematics Education, 2022)
Talk moves have been used as a communication tool for developing more productive mathematical discussions in school. To avoid uncritical adoption of a tool that was developed in a different context, it is important to consider cultural differences and concerns from the practice field. This study investigates group discussions among 15 Norwegian kindergarten teachers from seven kindergartens to explore how they understand talk moves, and what they consider to be possibilities and limitations of using talk moves in the Norwegian kindergarten context. We argue that kindergarten teachers’ concerns about talk moves do not seem to warrant rejection, but that professional efforts are required for meaningful enactment.